DAWKINS, Richard. Deus – Um delírio. São Paulo: Companhia das Letras, 2007. 520 p. - Selner, Claudiomir (Vox Scripturae - Revista Teológica Internacional, 2017)
DAWKINS, Richard. Deus – Um delírio. São Paulo: Companhia das Letras, 2007. 520 p.